Optimizing the Advancement of Islamic Education From the Lens of Islamic Law Philosophy - Silahuddin Silahuddin; Syamsul Rijal; M. Ikhwan; M. Agus Wahyudi (Seutia Hukamaa Cendekia, 2023)
This study explores the development of Islamic Education in Indonesia through the lens of Islamic legal philosophy. Since its birth, Islamic law has been known to adapt to the context of different times and places, thanks to its open-ended framework that allows for transformation in all things. This transformative potential presents an opportunity to modernize Islamic education. The research adopts a qualitative paradigm and interpretive approach, collecting data through a literature review and synthesizing and analyzing the findings. The findings of this study suggest that the contributions of Islamic law philosophy to the development of Islamic Education include: 1) Recognizing the philosophy of Islamic education, including Sufism, Rabbaniyyah, and Wujuduiyyah; 2) Avoiding the dichotomy between science and religion; 3) Revealing the unique essence, secrets, strengths, goodness, beauty, and benefits of Islamic education compared to other educational philosophies; and 4) Maintaining a balance between spirituality and modernity, to prevent moral and spiritual emptiness in modern society.